Access to prairie pollen affects honey bee queen fecundity in the field and lab - St. Clair, Ashley L.; Suresh, Sreelakshmi; Dolezal, Adam G. (Frontiers in Sustainable Food Systems, 2022)
Beekeepers experience high annual losses of colonies, with environmental stressors like pathogens, reduced forage, and pesticides as contributors. Some factors, like nutritional stress from reduced flower abundance or diversity, are more pronounced in agricultural landscapes where extensive farming limits pollen availability. In addition to affecting other aspects of colony health, quantity, and quality of pollen available are important for colony brood production and likely for queen egg laying. While some US beekeepers report >50% of colony loss in some years resulting from queen failure, the causes of poor-quality queens are poorly understood. Access to resources from native prairie habitat is suggested as a valuable late-season resource for honey bees that can reverse colony growth declines, but it is not clear how prairie forage influences queen egg laying. We hypothesized that the pollen resources present in an extensive Midwestern corn/soybean agroecosystem during the critical late season period affect honey bee queen egg laying and that access to native prairies can increase queen productivity. To test this, we designed a field experiment in Iowa, keeping colonies in either soybean or prairie landscapes during a critical period of forage dearth, and we quantified queen egg laying as well as pollen collection (quantity and species). Then, using pollen collected in the field experiments, we created representative dietary mixtures, which we fed to bees using highly controlled laboratory cages to test how consumption of these diets affected the egg laying of naïve queens. In 2 out of 3 years, queens in prairies laid more eggs compared to those in soybean fields. Pollen quantity did not vary between the two landscapes, but composition of species did, and was primarily driven by collection of evening primrose. When pollen representative of the two landscapes was fed to laboratory cages, queens fed prairie pollen laid more eggs, suggesting that pollen from this landscape, in some way, plays an important role in queen productivity. More work is needed to tease apart the drivers of these differences but understanding how egg laying is regulated is useful for designing landscapes for sustainable pollinator management and can inform feeding regimes for beekeepers.